The Role of Parents in Addressing the Discipline Problems of Children at School - Mollo, Nicholus Tumelo; Broer, Nico A.; van der Walt, Johannes L.; Wolhuter, Charl C.; Mampane, Kgale B. (Universitas Muhammadiyah Surakarta, 2024)
The study presented in this article explores a previously under-researched area: the role of parents in managing their children’s discipline problems in South African schools. Using a quantitative approach, researchers collected data through questionnaires from 212 parents in the North West province and 236 in Mpumalanga province. The findings highlight a shift in gender norms, with more fathers actively participating in addressing their children’s disciplinary issues. Several factors were found to influence parental involvement, including the parents’ age, the number of children they have, the school level (such as primary or secondary), the school type (such as public or private), and demographic characteristics. The study stresses that these factors must be taken into account when designing strategies to boost parental engagement in disciplinary matters. By offering valuable insights into parental roles and a legal perspective on school discipline, this research makes a significant contribution to the field of education. Based on the findings, the authors propose several recommendations. These include conducting awareness campaigns to challenge gender stereotypes, implementing parenting programs specifically aimed at fathers, designing initiatives tailored to different age groups, creating flexible engagement strategies for parents with multiple children, developing targeted programs for secondary and public schools, promoting the sharing of best practices, devising context-specific interventions, and offering training sessions for school governing body members to strengthen their capacity and encourage knowledge sharing among parents